Análisis del presupuesto del GAD Parroquial de Caracol del periodo 2018-2019 - Balarezo Vera, Lidia Esther (2021)
The budget of a company is a fundamental basis for its economic performance, since it depends on how the company, in this case, a GAD, can sustain its mandatory payments under the law, not to mention that this also, by be their income paid by the people, or the named users, know that these are the ones who comply with the letter with the necessary payments that the GAD merits, it should also be emphasized that for this study, it must be known that the GAD does not It is a company that must have income greater than its payments since it is a public entity of the government, so there must be a balance, our objective in this investigation is to determine if the GAD meets these requirements that are presented to achieve said objective .